ERP 시스템품질이 업무 효율성 및 의사결정 효율성과 활용성에 미치는 영향에 관한 연구 - 이정은(JeongEun Lee) (대한경영학회지, 2019)
최근 현대사회에서는 기업의 규모가 커지면서 기업 내 업무가 증가하고 관련 부서 간 필요한 정보를 공유하는 데 있어서 현재 사용하고 있는 시스템으로는 여러 가지 문제점 발생과 적시에 필요한 대응에 어려움을겪고 있다. 기업은 급변하는 경영 환경에서 문제가 발생했을 때 적시에 적절한 대응을 하는 것이 중요하다.따라서 기업은 정보시스템을 도입하여 회사 내 정보를 효율적이고 안전하게 이용할 수 있는 프로세스 구축이중요하며 이러한 정보시스템을 통합 합리적이고 전문적인 의사결정을 할 수 있어야 경쟁에서 우위를 점할수 있겠다.본 연구에서는 ERP 시스템의 품질이 ERP 시스템 효율성과 ERP 시스템의 활용성에 어떠한 영향을 미치는지에 대해 알아보기 위해 ERP 시스템의 품질을 시스템, 정보 및 서비스품질로 구분하여 이러한 시스템품질이업무효율성과 의사결정 효율성 및 시스템 활용성에 어떠한 영향을 미치는지를 검정하였다.본 연구에서 설문지를 통해 수집된 데이터를 IBM SPSS 25.0과 AMOS 25.0을 이용하여 코딩하여 분석을시행하였다. 집중타당성과 판별 타당성을 검증하기 위해 탐색적 요인분석을 하였고, 본 연구에서 설계된 모형구조의 타당성을 확인하기 위해 확인적 요인분석을 하였다. 또한, 변수들의 내적 일관성 신뢰도를 검증하기위해 신뢰도 분석을 하였으며, 마지막으로 경로 분석을 통해 본 연구의 가설을 검증하였다.첫째, ERP 시스템의 품질은 ERP 시스템 효율성에 유의한 영향을 미칠 것이다.라는 가설은 부분 채택되었다.시스템품질과 정보품질은 업무 효율성에 영향을 미치는 것으로 조사되었으나, 서비스품질은 업무 효율성에영향을 미치지는 못하는 것으로 조사되었다. 이는 서비스의 질 자체가 업무 효율성과는 직접적인 관계가 없다는것을 의미하는 데 서비스품질로 이용한 항목들이 ERP 시스템품질에 문제가 발생했을 때 대응속도 및 해결능력등을 포함하고 있으므로 문제가 발생했다는 것은 업무 효율성을 저하하기 때문에 이러한 결과가 도출되었다고생각한다.둘째, ERP 시스템의 효율성은 ERP 시스템 활용성에 유의한 영향을 미칠 것이다. 라는 가설은 모두 채택되었다. As company organizations grow in scale, indirect works such as office work are increasingin volume of late, making it difficult to share information across various departments. Numerousissues are emerging to inhibit the uninterrupted use of the legacy systems for this reason, makingit difficult to cope with them with the present system. It is important for companies to respondappropriately in a timely manner when problems arise in a rapidly changing business environment.Companies use information systems in all areas of accounting, human resources, purchasing,and sales. The impact of integrated information systems on job efficiency, decision making efficiencyand system utilization are becoming more important.Therefore, it is important to establish a process that enables companies to utilize informationefficiently and safely by introducing information systems. Not until the companies are able to makerational and professional decisions can competitive advantages be gained for them.This study is aimed at examining how the quality of the ERP system affects the efficiencyand utilization of the system. The quality of the accounting information system was divided intothe system quality, the information quality and the service quality in order to verify what impactthe aforementioned variables have on the job efficiency, decision-making efficiency, and systemutilization.The data collected in this study were analyzed with following conclusions using IBM SPSSstatistics version 25.0 for Windows and AMOS 25.0 after going through coding process.Exploratory factor analysis was conducted to verify the convergent validity and discriminantvalidity, and confirmatory factor analysis was conducted to confirm the validity of the model structuredesigned in this study. In addition, reliability analysis was conducted to verify the internal consistencyreliability of the variables. Finally, the hypotheses of this study were verified through path analysis. The results of this study are as follows:First, the hypothesis that the quality of the ERP system will have a significant impacton the efficiency of the ERP system was partially adopted. System quality and information qualitywere found to affect the job efficiency, but the service quality did not affect the job efficiency,suggesting that the quality of the service itself is not directly related to the job efficiency. This resultseems to be derived from the fact that the items used for the service quality includes the responsespeed and the resolution ability when there is a problem in the quality of the ERP system.Second, the hypothesis that the efficiency of the ERP system will have a significant impacton the ERP system utilization was accepted. KCI Citation Count: 0